Types of Conceptualization of Horror in the Genres of Country Noir and Southern Gothic - B. V. Rzayev (Концепт: философия, религия, культура, 2024)
The relevance of considering the semantic content of the concept of horror, which connects the genres of country noir and southern gothic into a single subsystem of cultural semiotics, is due to the need for a more detailed study of the specifics of both the generalizing concept itself and its role in specific genres of literature and cinema. Accordingly, the purpose of this study is to trace the features of the semantic registers of disclosing various types of horror in the philosophical and hermeneutic field of the genres of country noir and southern gothic. To do this, 1) the theoretical foundations for the conceptualization of horror in these genres are determined and the key elements and mechanisms of concept implementation are identified; 2) the narrative and metaphorical series of deployment of the concepts are analyzed within the framework of the lifeworlds of the characters in literary texts constructed by the authors; 3) philosophical and hermeneutic layers through which these concepts are revealed in selected genres are identified. The research methods are based on philosophical-hermeneutic, conceptual, and narrative approaches in the analysis of a number of works, chosen by their genre and the degree of their relevance for a particular type of conceptualization of horror. For example, the works No Country for Old Men by Cormac McCarthy, Winter’s Bone by Daniel Woodrell, The Salt of the Earth by Flannery O’Connor, The Last Good Kiss by James Crumley, The Sound and the Fury by William Faulkner, as well as the movie What Josiah Saw. The sequence of works referred to in the text is determined by the sequence of presentation of the types of the concept of horror. As a result of the study, the hypothesis was confirmed that the conceptualization of horror as a violation of the usual course of determination reveals itself in three versions of the ontologizing of this experience: horror of an uncertain world (determination dependent on the frame of perception of the subject, acting as an expression of the radical external, outside the power of the subject), horror of an indefinite self (determined as the order of the surrounding world with uncertainty in the inner world of the individual), horror of invasion (determination to displace each other). The conclusion is that the study of horror as a result of a violation of the usual course of determination in the context of country noir and southern gothic allows not only to identify their implicit philosophical and cultural component, but also to better understand these genres, as well as expand the theoretical basis for the analysis of similar phenomena in other cultural and literary traditions.